2017
DOI: 10.3329/ajmbr.v3i3.34527
|View full text |Cite
|
Sign up to set email alerts
|

Fry production and its marketing system of North-West fisheries extension project at Parbatipur, Dinajpur, Bangladesh

Abstract: Abstract:In order to understand the present status of hatcheries, questionnaire interview and participatory rural appraisal tools were used in North-west Fisheries Extension Project (NFEP), Parbatipur during the period from July to December 2015. There are two hatcheries in NFEP, Parbatipur-a carp hatchery and a prawn hatchery. The production of spawn was around 611 kg in the year 2015. According to the target hatchery manager collected brood fish from rivers and other sources which he maintained in their broo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 5 publications
3
20
0
Order By: Relevance
“…Aquaculture practices in Bangladesh started with natural seed but now it is almost entirely (99.55%) replaced by hatchery produced seed, while supply of fingerlings is considered as a prerequisite for the development of aquaculture (Al-Asif et al, 2014;Ali et al, 2018;Faruk et al, 2018;Islam et al, 2017;Webber and Riordan, 1976). Since 1975, artificial fish breeding techniques and low cost hatchery designs have been successfully adapted in Bangladesh (Islam et al, 2016(Islam et al, , 2017. Mirror carp (C. carpio var.…”
Section: Introductionmentioning
confidence: 99%
“…Aquaculture practices in Bangladesh started with natural seed but now it is almost entirely (99.55%) replaced by hatchery produced seed, while supply of fingerlings is considered as a prerequisite for the development of aquaculture (Al-Asif et al, 2014;Ali et al, 2018;Faruk et al, 2018;Islam et al, 2017;Webber and Riordan, 1976). Since 1975, artificial fish breeding techniques and low cost hatchery designs have been successfully adapted in Bangladesh (Islam et al, 2016(Islam et al, , 2017. Mirror carp (C. carpio var.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, there is a great potential of crab culture throughout the coastal area in Bangladesh. Millions of poor fishers, traders and transporters are directly or indirectly dependent on crab fishery in Bangladesh (Zafar and Ahsan, 2006;Hossain et al, 2018;Hossain et al, 2015;Asif et al, 2014;Rahaman et al, 2015;Islam et al, 2017;Leela et al, 2018;). The mud crab was first exported in 1977-78 fiscal year and become a stable business in 1982.…”
Section: Introductionmentioning
confidence: 99%
“…The analyzed mean moisture content of fish feed varied from 7.43% to 15.33%. Dry feeds contain 8-10% moisture while the water content of moist feed ranges from 17 to 40% or more (Lall, 1991;Zaman et al, 2017;Islam et al, 2017b;Haq et al, 2017;Rahman et al, 2018;Rahman et al, 2019;Biswas et al, 2018 andYeasmin et al, 2018). Roy (2002) reported that a diet containing 9.8% moisture appears to be more suitable for GIFT tilapia.…”
Section: Discussionmentioning
confidence: 99%